HARDINESS DAN DUKUNGAN SOSIAL DENGAN ADAPTABILITAS KARIER PADA MAHASISWA FAKULTAS PSIKOLOGI - Yolanda; Wiwik Sulistiani; Dewi Mahastuti (Jurnal Psikologi Poseidon, 2022)
The research aims to determine the existence of: (1). The relationship between career hardiness and career adaptability; (2). The relationship between social support and career adaptability; (3). The relationship between hardiness and social support with career adaptability in Psychology Faculty students, Hang Tuah University, Surabaya. The research uses a quantitative approach to survey research methods. The number of subjects is 194 students. The sampling technique in this study used quota sampling. Data analysis used product moment and multiple correlation. The career adaptability scale consists of 24 items (α=0.914). Hardiness scale consists of 18 items (α=0.831). The social support scale consists of 12 items (α=0.956). The major hypothesis obtained F value sig. Change of 0.003 is less than 0.05. The close relationship between hardiness and social support with career adaptability is 6%. These results indicate that the hypothesis is accepted, meaning that there is a positive relationship between hardiness and social support with career adaptability for students of the Psychology Faculty, Hang Tuah University, Surabaya. From these results, there are several implications including being able to contribute to development institutions related to career adaptability and can be a useful reference for the development of student knowledge.